Pengaruh Overconfidence Dimoderasi Gender terhadap Keputusan Investasi pada Generasi Milenial di Karawang - Simbolon; Paulina Karolin; Situngkir, Tiar Lina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to examine the influence of overconfidence on investment decisions of the millennial generation in Karawang and evaluate whether gender variables can moderate this relationship. This research uses a survey research design. There is an independent variable, namely overconfidence and a dependent variable (dependent) investment decisions. This research focuses on the millennial generation population in Karawang, which numbers around 1,029,290 people. Meanwhile, the sample used was the millennial generation in Karawang who were active in investment activities, totaling 268 respondents. In this research, verification analysis uses Simple Linear Regression Analysis to test whether or not there is an influence of overconfidence on investment decisions. The next test to see whether the influence of the moderating variable (gender) can strengthen or weaken the overconfidence variable on investment decisions, the Moderated Regression Analysis (MRA) test is used. The research the results show that overconfidence has an influence on the investment decisions of the millennial generation. This generation tends to make investment decisions with a high level of self-confidence, which can lead to investment risks. However, gender is not able to moderate the relationship between overconfidence and investment decisions, meaning that both men and women show the same pattern regarding the influence of overconfidence on their investment decisions. Based on these findings, it is recommended to improve financial education to help the millennial generation make more rational and wise investment decisions.